Did Parental Involvement Laws Grow Teeth? The Effects of State Restrictions on Minors' Access to Abortion - Caitlin Knowles Myers; Daniel Ladd (Institute of Labor Economics (IZA), 2017)
We compile data on the locations of abortion providers and enforcement of parental involvement laws to document dramatic increases in the distances minors must travel if they wish to obtain an abortion without involving a parent or judge. Between 1992 – the year the U.S. Supreme Court established the undue burden standard in Planned Parenthood v. Casey – and present, the average distance to a confidential abortion has increased from 55 to 454 miles. Using both double and triple-difference estimation strategies, we estimate the effects of parental involvement laws, and allow these effects to vary with the distances minors might travel to avoid them. Our results confirm previous findings that parental involvement laws did not increase teen births in the pre-Casey era, and provide new evidence that in more recent decades they have increased teen birth by an average of 3 percent. The estimated effects are increasing in avoidance distance to the point that a confidential abortion is more than a day's drive away, and also are 4 to 6 times greater in counties with high rates of poverty. We estimate that over the past 25 years, parental involvement laws have resulted in half a million additional teen births.
Keywords: I11; I12; J13; 330; abortion; fertility